State of the art/science: Visual methods and information behavior research - Hartel, J.; Sonnenwald, D.; Lundh, Anna Hampson; Fried Foster, N. (2012)
This panel reports on methodological innovation now underway as information behavior scholars begin to experiment with visual methods. The session launches with a succinct introduction to visual methods by Jenna Hartel and then showcases three exemplar visual research designs. First, Dianne Sonnenwald presents the "information horizon interview" (1999, 2005), the singular visual method native to the information behavior community. Second, Anna Lundh (2010) describes her techniques for capturing and analyzing primary school children's information activities utilizing video recordings. Third, Nancy Fried Foster (Foster & Gibbons, 2007) reports how students, staff and faculty members produce maps, drawings, and photographs as a means of contributing their specialist knowledge to the design of library technologies and spaces at the University of Rochester. Altogether, the panel will present a collage of innovative visual research designs and engage the associated epistemological, theoretical, methodological, and empirical issues. All speakers will have 15 minutes and be timed to allow a minimum of 30 minutes for audience questions, comments, and discussion. Upon the conclusion attendees will have gained: knowledge of the state of the art/science of visual methods in information behavior research; an appreciation for the richness the approach brings to the specialty; and a platform to take new visual research designs forward.